Consumer attitudes towards food safety risks associated with meat processing - Christiane Schroeter (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2001)
A focus group study with 37 residents of Manhattan, Kansas, was conducted to examine consumers' risk perceptions of foodborne illnesses from beef. The four focusgroup sessions were designed to determine (1) relative preferences for alternative combinations of public food safety (Hazard Analysis and Critical Control Points (HACCP), carcass pasteurization, irradiation) and private protection (home preparation of rare, medium, and well-done hamburgers); (2) how who is at risk (children vs. adults) influences preferences; (3) whether consumers would pay a premium for the higher levels of product safety arising from the adoption of three different innovations in processing plants; and (4) how to improve risk communication about foodborne illnesses and ways to protect against them. Although participants seemed aware of many food safety practices, misinformation and misconception also were found. The majority of the participants preferred well-done, steam-pasteurized or medium, irradiated hamburgers. For a 5-year-old child, the majority chose well-done, steampasteurized or well-done, irradiated hamburgers. Concerning willingness-to-pay, the majority of the participants preferred steam-pasteurized ground beef to regular ground beef when both were priced equally. Results indicated that new technologies available for food safety interventions provided a marginal value to participants. Participants also expressed a need for more information.
Keywords: 330; Lebensmittelbelastung; Rindfleisch; Konsumentenverhalten; Risikopräferenz; USA